The connections world the future of Asian capitalism - Commander, Simon 1953-; Estrin, Saul 1952- (Cambridge University Press, 2022)
A central feature of modern Asia that trumps differences in economic and political systems is the web of close relationships running between and within business and politics; the connections world. These networks facilitate highly transactional interactions yielding significant reciprocal benefits. Although the connections world has not as yet seriously impeded Asia's economic renaissance, it comes with significant costs and fallibilities. These include the creation and entrenchment of huge market power and the attenuation of competition. They in turn hold back the growth in productivity and innovation that will be essential for further development. The connections world also breeds massive inequalities that may culminate in political instability. The authors argue that if Asia's claim to the 21st century is not to be derailed, major changes must be made to policy and behaviour so as to cut away the foundations of the connections world and promote more sustainable economic and political systems